Anestesia em facectomia com facoemulsificação: delineamento crítico da vigente prática clínica adotada por especialistas no Brasil - Fernandes, Thyago Araújo (2018)
There is no consensus on how to perform anesthesia for cataract surgery. This study aimed the evaluation of the anesthetic management of candidates for phacoemulsification, a practice overview of members of the Brazilian Society of Anesthesiology. The research had a cross-sectional observational profile, covering the entire national territory, in 2018. A questionnaire was applied with SurveyMonkey software. The amount of 145 physicians were included, 60% male, aged between 25 and 44 years (66%) and with professional experience greater than five years in ophthalmological surgeries (61%). Brazilian regions with the most expressive participation were Southeast (33%) and Northeast (30%). Regional anesthesia was the main technique (64%), specially the peribulbar block (53%). Professional experience greater than five years (p 0.019) and non-exclusive practice in public health institutions (p 0.041) were identified as factors significantly related to regional anesthesia. Sedative drugs were used by almost all the interviewees (96%), specially with benzodiazepines and opioids. Almost 52% prefer local anesthetics mixtures in blocks. Vasoconstrictors are administered by 22%. Single injection block was preferred among 63%; with p 0.029 and p <0.001 were respectively associated to regional anesthesia practice in non-exclusively public healthcare institutions and usage of low volume of anesthetic solution. Regarding the total volume of anesthetic solution, 66.2% use up to 6 mL. Adjuvant drugs was reported by 68% of the physicians, specially hyaluronidase (85,4%) in this group. Eyelid ptosis (61,4%) and paralysis of ocular movements (88,3%) were indicated as the most observed parameters in the evaluation of regional blocks. The most frequent adverse events in regional anesthesia were chemosis (60%) and pain during injection of the anesthetic solution (31%). We determined the profile of anesthesia for phacoemulsification in Brazil: sedation is performed along with regional techniques, mainly the peribulbar block, with low volume of anesthetic solution, along with hyaluronidase as adjuvant.